Mapping Skills Education Through Social Media Platform For Technical Vocational Education And Training (TVET) In Malaysia - Soon, Eu Hui; Baharun, Sabariah; Manaf, Nur'azah Abdul; Mahrin, Naz'ri (School of Social Sciences, USM, 2017)
Web 2.0 applications have evolved significantly in producing high quality learning environments where the effects can cater for Technical Vocational Education and Training (TVET) learning pathways. In the shift to the Fourth Industrial Revolution, information and communication technology involving new media elements such as social media applications have impacted society in many aspects relating to thinking, cultural and economic diversities. As social media shows an exponential growth in our daily usage, TVET and the skills education pathways can adopt this digital trend to conform to a collaborative learning experience. This research presents a conceptual framework by adapting graph theory analytics to map specific skill sets that can conform to the National Occupational Skills Standards (NOSS) in correlation to the learning outcome domains of the Malaysian Qualifications Framework (MQF) through a personalized social media platform. Sampling only selected sub-sectors within the NOSS registry, this research aims to apply social media mechanics in enabling a strong network of collaborators to enhance the TVET learning experience. Subsequently, this research adds value in the sampling enhancement of current outdated NOSS, as well as reviewing the ability in mapping new jobs for the future.